Advanced glycation end products regulate the receptor of AGEs epigenetically - Wu, Xiaoqing; Shi, Xuanren; Chen, Xiaoyong; Yin, Zhanhai (Frontiers in Cell and Developmental Biology, 2023)
Advanced glycation end-products (AGEs) can boost their receptor of AGE (RAGE) expression through the downstream signaling pathway to facilitate AGE–RAGE interaction. In this regulation process, the primary signaling pathways are NF-κB and STAT3. However, the inhibition of these transcription factors cannot completely block the upregulation of RAGE, which indicates AGEs may also impact RAGE expression via other pathways. In this study, we revealed that AGEs can exhibit epigenetic impacts on RAGE expression. Here, we used carboxymethyl-lysine (CML) and carboxyethyl-lysine (CEL) to treat liver cells and discovered that AGEs can promote the demethylation of the RAGE promoter region. To verify this epigenetic modification, we employed dCAS9-DNMT3a with sgRNA to specifically modify the RAGE promoter region against the effect of carboxymethyl-lysine and carboxyethyl-lysine. The elevated RAGE expressions were partially repressed after AGE-induced hypomethylation statuses were reversed. Additionally, TET1 were also upregulated in AGE-treated cells, indicating AGEs may epigenetically modulate RAGE through the elevating TET1 level.